Pengaruh Budaya Organisasi dan Etos Kerja Terhadap Kinerja Karyawan PT Muara Krakatau Semarang - Joseph Jhonson Chris Marantika; Ratnaningrum Ratnaningrum (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
This study aims to examine the influence of organizational culture and work ethic on the performance of employees of PT Muara Krakatau in Tengaran District, Semarang Regency. Respondents in this study were employees of the sewing section of PT. Muara Krakatau, Semarang Regency, totaling 90 employees. The method used to obtain information data is through a questionnaire. The analytical technique used in this research is multivariate regression analysis. The results showed that there was a positive influence of organizational culture and work ethic on the performance of employees of PT. Muara Karang. It is suggested that to improve employee performance the company must improve organizational culture and work ethic.